Bounded rationality and autonomy of Political Science - Mussi, Daniela (Universidade Estadual Paulista / UNESP, 2017)
The article aims to present and discuss aspects of the crisis that drove in the 1940s and 1950s in the United States the emergence of a new way of thinking Political Science as a discipline. For it shows the birth of the “behaviorist era” when the old American liberalism began to be challenged in its foundations. As a result, it highlights the contributions that showed the need to form a new disciplinary field that could bring together political theory and empirical research. It exemplifies the emergence of the concept of bounded rationality as a theoretical immediate result of this process, and discusses its implications and limitations.